Individual and Combined Association between Unhealthy Lifestyle Behaviors and Body Weight Dissatisfaction in a Sample of Adolescents from Southern Brazil - Suellem Zanlorenci; Leticia Gonçalves; Tiago Rodrigues de Lima; Diego Augusto Santos Silva (MDPI AG, 2023)
The individual and combined association between unhealthy lifestyle behaviors and body weight dissatisfaction in adolescents was investigated. This cross-sectional research used data from 676 students (348 female), aged between 14 and 19 years old (mean of 14.6 years old) from southern Brazil. Unhealthy lifestyle behaviors and body weight dissatisfaction were assessed through a questionnaire. Unhealthy lifestyle behaviors included smoking, excessive alcohol consumption, sedentary lifestyle, and poor diet, and were analyzed as individual factors and as combinations of behaviors. For males, smoking (OR: 2.6; 95% CI: 1.6-4.0) and the combination of smoking/excessive consumption of alcoholic beverages (OR: 2.5; 95% CI: 1.1-5.8) were directly associated with the desire to reduce body weight, whereas the combination of smoking/inadequate diet (OR: 1.3; 95% CI: 1.0-1.6) was associated with the desire to increase body weight. For females, the combinations of inadequate diet/physical inactivity (OR: 1.6; 95% CI: 1.0-2.5) and of smoking/excessive consumption of alcoholic beverages (OR: 1.9; 95% CI: 1.4-2.8) were directly associated with the desire to reduce body weight. The presence of simultaneous unhealthy lifestyle behaviors is associated with bodyweight dissatisfaction in adolescents.